Severe undernutrition increases bleeding risk on vitamin-K antagonists. Issue 4 (April 2021) - Moustafa, Farès; Dopeux, Loïc; Mulliez, Aurelien; Boirie, Yves; Morand, Christine; Gentes, Elodie; Farigon, Nicolas; Richard, Damien; Lebreton, Aurélien; Teissandier, Dorian; Dutheil, Frederic; Schmidt, Jeannot
Summary: Introduction: Hemorrhage occurs in 7–10% of patients treated with vitamin K antagonist (VKA), with major bleeding in 1–3%. Impact of nutritional status on the bleeding risk of patients on anticoagulants is still poorly documented. Our study aimed to analyze the link between the nutritional status of patients on VKA and the occurrence of hemorrhagic events. We also analyzed micronutrients status. Methods: A case–control, monocentric, and prospective study was conducted from August 2012 to October 2015. The case patients were those presenting with major bleeding and control patients those without any bleeding under VKA treatment. Results: Overall, 294 patients under VKA treatment were paired according to age, gender, and index normalized ratio (INR). Out of these, 98 (33.3%) had major bleeding and 196 (66.7%) did not have any bleeding. Additionally, more than two-thirds of patients displayed undernutrition, which was more prevalent in bleeding than non-bleeding patients (OR = 1.85, CI95%: 1.07–3.21). There was a higher bleeding risk for those with severe undernutrition (OR = 2.66, CI95%: 1.58–4.46), with no difference found concerning moderate undernutrition. Bleeding patients had lower plasma-zinc concentrations than non-bleeding patients (9.4 ± 3.6 vs. 10.5 ± 3.7 μmol/L, p = 0.003); among them, there was a higher rate of patients with plasma zinc under 5 μmol/L (9% vs. 2%, p < 0.001). Conclusion: Patients with undernutrition on VKA exhibit a significantly higher bleeding risk, which increases three-fold in case of severe undernutrition. The evaluation of nutritional status provides additional, valuable prognosis information prior to initiating VKA therapy. ClinicalTrials.gov number: NCT 01742871.